Urbanization and electric vehicle adoption: exploring direct and indirect economic growth-mediated pathways - Law, Teik Hua; Yang, Kun (Elsevier, 2025)
This study analyzes the transition from internal combustion engine vehicles (ICEVs) to electric vehicles (EVs) across 31 countries from 2010 to 2023 and identified an inverted U-shaped relationship between GDP per capita and electrification. Evidence confirms an Environmental Kuznets Curve (EKC) pattern, where EV adoption accelerates only after a national income threshold of approximately $15,914 is surpassed. Urbanization influences this transition through direct pathways (e.g., infrastructure and policy in moderately dense cities) and indirect pathways mediated by economic growth, though this mediation is contingent on educational attainment. The analysis also reveals a U-shaped effect for urbanization, where hyper-dense urbanized areas can see reversals due to high public transport use. Furthermore, it highlights significant spatial inequalities as rural areas lag in adoption due to a lack of charging infrastructure and financial incentives. Results underscore the need for tailored policy interventions that align economic development and urban planning with sustainable mobility goals.